2021
DOI: 10.1108/ijaim-11-2020-0188
|View full text |Cite
|
Sign up to set email alerts
|

Real earnings manipulation surrounding mergers and acquisitions: the targets’ perspective

Abstract: Purpose This paper aims to investigate whether UK public targets manage their earnings using real activities manipulation in the period prior to the announcement of a mergers and acquisition (M&A). It also examines whether the payment method in M&As affects the degree to which takeover targets manipulate earnings. Design/methodology/approach Using a sample of 131 UK listed targets acquired over the period 1995–2013, this paper examines real earnings management (REM) by employing OLS regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 102 publications
(136 reference statements)
1
13
0
Order By: Relevance
“…The payment method of the transaction can be stocks, cash or a combination of both. The deal value is more than one million to exclude deals made by a very tiny target (Ahmed and Elshandidy, 2021; Elrazaz et al , 2021). The M&A transaction is completed, and the acquisition deal represents more than 50% of the target firm.…”
Section: Methodsmentioning
confidence: 99%
“…The payment method of the transaction can be stocks, cash or a combination of both. The deal value is more than one million to exclude deals made by a very tiny target (Ahmed and Elshandidy, 2021; Elrazaz et al , 2021). The M&A transaction is completed, and the acquisition deal represents more than 50% of the target firm.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing only on Taiwanese listed acquirers enables us to calculate CAR (cumulative abnormal returns). Following prior research (e.g., Ahmed et al, 2022;Elrazaz et al, 2021), we set the following criteria to define our final sample. Financial firms (SIC 6000-6999) and utilities (SIC 4900-4999) are excluded from the sample, since they are subject to regulatory constraints and different accounting considerations (Basu et al, 2009).…”
Section: Samplementioning
confidence: 99%
“…(CAR). Following prior research(Ahmed et al, 2022;Elrazaz et al, 2021), we set the following criteria to define our final sample. Financial firms (SIC 6000-6999) and utilities (SIC 4900-4999) are excluded from the sample, as they are subject to regulatory constraints and…”
mentioning
confidence: 99%
“…(2021) emphasized that firms of stock-based deals have more incentives for earnings management because the inflated profitability influences the market firm value, diminishing the acquiring cost. More recently, Campa and Hajbaba (2016) and Elrazaz et al . (2021), adopting different notions and demonstrating contradictory results, both follow the contemporary literature, incorporating additionally real earnings management measures in their proposed approaches, providing findings that enrich the existing knowledge about the target firm's strategic behavior.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The preference for real earnings management is attributed to the fact that real earnings management methods are more difficult to be detected than accounting practices. More recently, Elrazaz et al. (2021), in contrast to Campa and Hajbaba (2016), found that target firms only in-stock deals engage in real-activities manipulations with the method of cutting the discretionary expenses and not with sales and production costs manipulation.…”
Section: Literature Reviewmentioning
confidence: 99%